THE ROLE OF TEACHERS IN EDUCATION. - Axmedova Sitora Eminjin qizi; Axunova Shaxzoda Qurbonali qizi; Gaforov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article about is the role of teachers in education. Teachers play an quintessential position in education ,most specifically in the lives of the college students they in the classroom. What define a instructor is her/his potential to train students and a high quality affect on them. Generally ,the function of atrainer in education gose past teaching . In today's world, teaching has different faces and a teacher has to raise out the phase of being an exterior parent ,counselor,mentor,function model and so on.